Resilient blunderers: credit rating fiascos and rating agencies' institutionalized status as private authorities. Issue 5 (27th May 2016) - Kruck, Andreas
ABSTRACT: The authority of credit rating agencies (CRAs) has been surprisingly resilient even in the face of recurrent, widely recognized and severe rating failures. This contribution analyses why rating fiascos have had little impact on CRAs' status as transnational private authorities. This resilience is not only owing to CRAs' own (genuinely private) sources of authority. Rather, previous public authorization of CRAs as quasi-regulators and the path-dependent politics of post-fiasco re-regulation have institutionally entrenched and legitimated their status as private authorities. Relying on a historical institutionalist approach and focusing on the regulatory setting of the European Union (EU), the article retraces how flawed public policy choices in the past, i.e., granting CRAs a recognized regulatory role, and non-intended institutional dynamics have spawned later regulatory dilemmas in dealing with CRAs' rating fiascos. Thus, CRAs' recent mistakes have paradoxically fostered a progressive institutionalization rather than a downgrade of their role as private governors.